An Analysis of the Auteurship of Oliver Jeffers - R, Diya Phutane (Journal of Advanced Research in Journalism & Mass Communication, 2023)
Visual storytelling is a part of everyone’s life. Images, art, and design are what we are exposed to from a young age be it, in films, videos, magazines, books etc. Picture books are one such medium that is an essential part of one’s childhood. Everyone grew up reading their favourite book, which had vibrant and eye-catching illustrations to accompany the story. To read a picture book is to have a wholesome experience. It is one where we get to experience the coming together of design, storytelling, illustrations and so on. It is an art form that enriches the lives of not only young children but adults who have a keen interest in telling stories, and who have a wild imagination and eye for beautifully made illustrations and visuals. This study aims to explore and analyse the work of award-winning author and illustrator - Oliver Jeffers. The books “Here we are: Notes for living on planet earth” (2017) and “This moose belongs to me” (2012) will be used as samples for this study of auteur theory. A qualitative methodology and content analysis will be done on the characteristics of auteur theory as proposed by Andrew Sarris (1962) and will be applied to the illustrations in the books to find consistency in Oliver Jeffers’s works. The resulting answer will help us to understand if Oliver Jeffers can be considered an auteur in his field of expertise. How to cite this article: Phutane RD. An Analysis of the Auteurship of Oliver Jeffers. J Adv Res Jrnl Mass Comm 2023; 10(2): 16-21. DOI: https://doi.org/10.24321/2395.3810.2023010